The quest for the fictional Jesus : gospel rewrites, gospel (re)interpretation, and christological portraits within Jesus novels /: gospel rewrites, gospel (re)interpretation, and christological portraits within Jesus novels. (2017) - Ramey, Margaret E
No abstract available